Plant-Based Diet to Reverse/ Regress Vulnerable Plaque: A Case Report and Review - Mulijono, Dasaad; Hutapea, Albert M; Lister, I Nyoman E; Sudaryo, Mondastri K; Umniyati, Helwiah (Archives of Clinical and Medical Case Reports, 2024)
A considerable proportion of fatalities resulting from acute myocardial infarction (AMI) occur suddenly in asymptomatic patients. Approximately 68% of AMIs are caused by coronary stenosis ≤ 50%, which is most likely due to the rupture of vulnerable plaques (VPs). A 55-year-old asymptomatic cardiologist who had been following preventive measures according to international guidelines and had reasonable metabolic-laboratory parameters underwent a cardiac check-up involving the use of coronary artery calcium (CAC) and computed tomography coronary angiography (CTCA), which revealed the presence of VP causing 50% stenosis in his proximal left anterior descending artery (LAD). Recognizing that his previous preventive measures, which were adopted from the guidelines, had failed to protect him from developing atherosclerosis, he chose to adopt a plant-based diet (PBD) while continuing on optimal medical therapy (OMT). After three years, there was a substantial regression in his CAC score and stenosis. The PBD program he adopted was specifically designed, taking into consideration the quality, quantity, and method of food processing, as well as the consumption of specific vitamins and minerals. This case report and review emphasize the importance of prevention to avoid the development of atherosclerosis or VP, especially in high-risk patients. Prevention involves not only the use of OMT but also the modification of one's lifestyle, particularly the adoption of a healthy and proper diet that can prevent the development of atherosclerosis, reduce inflammation, and promote the regression and stabilization of vulnerable plaques if they have already formed. The case also highlights CAC and CTCA as the most efficient, practical, reliable, safe, and economical methods for identifying VPs. The tests are widely accessible in most cardiac centers. Thus, we offer a novel, non-invasive diagnostic method for diagnosing VP and provide the most practical, efficient, and affordable approach to regress or stabilize VP. Consequently, the current guidelines for managing chronic coronary syndrome (CCS) are recommended to be revised. Specifically, it is suggested that the guidelines be amended to advise high-risk asymptomatic patients to consider the role of CAC and CTCA. Additionally, it is recommended that lifestyle modifications be reinforced in conjunction with OMT to manage VP and promote regression and reversal of atherosclerosis effectively.